Continuous Spinal Anaesthesia for Intertrochanteric Femur Fracture in a Patient with Skeletal Dysplasia - Sharad Khakurel; Rupesh Kumar Yadav (Case Reports in Anesthesiology)
The practice of continuous spinal anaesthesia is not common. Though underutilised, it offers significant advantage when compared to the single-shot technique nonetheless. Time and again, it has proven its worth in patients with advanced cardiac illness, spinal deformities, and obesity. We here successfully employed this neuraxial anaesthetic technique in a sixty-two-year-old male patient with skeletal dysplasia, who presented for surgical fixation of intertrochanteric fracture of the femur. With short stature, anticipated difficult airway, and poor pulmonary status complicating the anaesthetic plan, we opted for continuous spinal anaesthesia. The procedure was carried out uneventfully with 8 mg of hyperbaric bupivacaine used in titration to anaesthetic needs. Patients with skeletal dysplasia present with wide array of clinical conditions that pose a formidable challenge to anaesthesiologists. Continuous spinal anaesthesia can be safely practiced in such patients as it provides a titratable form of neuraxial blockade with reduced dose of local anaesthesia. This, in turn, ensures a predictable block and, thus, hemodynamic stability.